Effect of cyclic high temperature fluctuations on the corrosion failure of S40900, S43036, S31635 and S44400 stainless steels. Issue 1 (1st January 2021) - Loto, Roland Tolulope
ABSTRACT: Corrosion resistance of untreated S40900, S43036, S44400 and S31635 stainless steels (S409, S430, S444 and S316) in 0.05 M H2 SO4 /3.5% NaCl solution was investigated and compared to their heat-treated counterparts after cyclic temperature variation between 1000°C and 37°C by potentiodynamic polarization, potentiostatic analysis, open circuit potential measurement and optical microscopy. Results showed untreated S409 exhibited the weakest resistance to corrosion at 8.406 mm/y while untreated S316 displayed the highest resistance at 1.581 mm/y. Cyclic heat treatment caused significant increase in corrosion rate of untreated S409, S430 and S444 by 21.92%, 38.46% and 94.76%. Corrosion rate of untreated S316 decreased by 69% to 0.490 mm/y. Untreated and heat-treated S316 exhibited the least metastable pitting tendency while heat-treated S409 and S430 exhibited the highest. Untreated S444 showed the highest tendency to passivate compared to heat-treated S409 and S430 with the lowest tendency. Heat treatment generally improved passivation rate, but not passivation resilience. Untreated S444 and heat-treated S430 exhibited the widest passivation range. Heat treatment increased the tendency for pit formation on the steels. Plots from open circuit potential measurement showed untreated S444 exhibited the lowest thermodynamic tendency to corrode with potential culminating at −0.201 V while among the heat-treated steels, S316 displayed the lowest corrosion tendency peaking at −0.288 V. Corrosion pits on heat-treated S409 were significantly larger compared to the untreated steel. Superficial corrosion pits visible on untreated S430 disappeared after heat treatment. Heat treatment decreased the occurrence of corrosion pits on S316 while miniature corrosion pits were present on heat-treated S444.